Автоматичні системи регулювання з цифровими ПІД-регуляторами, увімкненими за схемами послідовної та послідовно-паралельної корекції - Ковела, Іван (Видавництво Національного університету «Львівська політехніка», 2002)
Dynamic features of ACS with different switching schemes for digital PIDcontroller of parallel structure are under investigation. The advantages of systems which provide parallel correction of object by means of PID-algorithm proportional and differential partials are highlighted.